2018
DOI: 10.1038/s41598-018-32438-7
|View full text |Cite
|
Sign up to set email alerts
|

Psoralen induced cell cycle arrest by modulating Wnt/β-catenin pathway in breast cancer cells

Abstract: Psoralen could inhibit the proliferation of human breast cancer cells, however, the molecular mechanism was unclear. We evaluated the anti-proliferative effects of psoralen by MTT, plate colony formation assay and cell cycle analysis in MCF-7 and MDA-MB-231 cells. The effects of psoralen on activation of Wnt/β-catenin and the related target genes were examined by quantitative real-time PCR, western blotting and cell immunofluorescence. The tumor growth was conducted in BALB/c nude mice and the pathological cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 22 publications
2
26
0
Order By: Relevance
“…Psoralen arrests at G1 phase in SMMC7721 by Cyclin-E1 reduction [73]. Psoralen arrests G0/G1 by deregulation of Wnt/β-catenin in MCF-7 [93].…”
Section: Cell Cycle Arrestmentioning
confidence: 98%
“…Psoralen arrests at G1 phase in SMMC7721 by Cyclin-E1 reduction [73]. Psoralen arrests G0/G1 by deregulation of Wnt/β-catenin in MCF-7 [93].…”
Section: Cell Cycle Arrestmentioning
confidence: 98%
“…Wang et al found that psoralen increased the expression of Axin-2, a negative regulator of the Wnt/b-catenin/TCF signaling pathway, in MCF-7 and MDA-MB-231 cells, and decreased the expression of b-catenin and its downstream target Fra-1. Additional studies confirmed that psoralen induced cell cycle arrest in breast cancer cells by regulation of the Wnt/b-catenin pathway (Wang et al, 2018). Cyclin D1 and Cyclin E1 play important roles in cell cycle regulation, acting as positive regulators of cyclin-dependent kinase (CDK).…”
Section: The Anti-tumor Effects Of Psoralen Increasing Endoplasmic Rementioning
confidence: 84%
“…Interestingly, Xin et al found that psoralen, an estrogen receptor alpha (ERa) agonist, significantly promoted the proliferation of MCF-7 cells (Xin et al, 2010). However, as previously described, psoralen markedly inhibited the proliferation of MCF-7 cells by inducing G0/G1 phase arrest (Wang et al, 2018). Therefore, the effect of psoralen in MCF-7 cells requires additional exploration.…”
Section: The Anti-tumor Effects Of Psoralen Increasing Endoplasmic Rementioning
confidence: 95%
“…1 ), was reported to have significant antibacterial effects on the periodontal pathogen P. gingivalis, and was found to inhibit the inflammatory response induced by it 11 . Psoraleae has also been shown to possess strong anti-osteoporosis effects 12 , inhibit tumor growth 13 , and exhibit estrogen-like effects 14 .
Figure 1 Molecular structure of fructus psoraleae’s extract psoralen.
…”
Section: Introductionmentioning
confidence: 99%